Validation of a Perception of Objectification in the Workplace Short Scale (POWS) - Crone, Lola; Brunel, Lionel; Auzoult, Laurent (Frontiers in Psychology, 2021)
An increasing number of studies focus on the phenomenon of objectification in the workplace. This phenomenon reflects a process of subjection of the employee, where he is considered as an object, a mean (utilitarian) or reduced to one of his attributes. Previous studies have shown that objectification can have consequences on the workplace health or performance. Field studies are based on objectification measures based on tools whose psychometric qualities are unclear. Based on the Auzoult and Personnaz (2016a) objectification in the workplace scale, we conducted a study with the aim of devising a new parsimonious scale. We present three studies which aim to validate this new scale. In the first study, an EFA and a CFA were performed in order to construct a scale and verify its structure validity. We obtained a 10-item scale reporting two factors labeled "Instrumental value" and "Powerfulness ". The psychometric qualities of this scale were satisfactory, i.e. showed good internal reliability and good structural validity. In a second study, we tested the convergent and divergent validity of the scale. We observe that POWS is adequately correlated with dehumanization indicators. Finally, in a third study, we found that only powerfulness was associated with negative consequences for occupational health. This suggests that objectification is a process of social perception that contributes either to the devaluation of social agents in the workplace or to normal functioning at work.